2017
DOI: 10.1590/2359-3997000000315
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of insulin resistance among Brazilian chronic hepatitis C patients

Abstract: Objective: This study aims to estimate the prevalence of insulin resistance (IR) among chronic hepatitis C (CHC) patients and their related laboratory and demographic data. Subjects and methods: In this study, non-diabetic CHC patients referred to Viral Hepatitis Ambulatories from Rio de Janeiro (Brazil) donated blood samples. Insulin was measured using a chemiluminescence immunoassay. IR was determined by HOMA-IR, where HOMA-IR > 2 was defined as IR. Results: A total of 214 CHC patients were recruited (123 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Various hepatic and/or extrahepatic manifestations of HCV infection can contribute to renal deterioration. Insulin resistance is associated with HCV-induced hepatic dysfunction and has been found in 10% to 60% of HCV-infected patients [ 16 - 18 ]. However, recent experimental studies have demonstrated that the HCV core protein interferes with insulin signaling by degrading insulin receptor substrate-1 by upregulating the expression of mammalian target of rapamycin (mTOR)/p70 ribosomal protein S6 kinase 1, suppressor of cytokine signaling 3, and tumor necrosis factor-α [ 19 , 20 ]; and downregulating glucose transporter 2,4 expression through upregulation of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase 2 [ 21 , 22 ].…”
Section: Clinical Impact Of Hcv Infection In Ckd Patientsmentioning
confidence: 99%
“…Various hepatic and/or extrahepatic manifestations of HCV infection can contribute to renal deterioration. Insulin resistance is associated with HCV-induced hepatic dysfunction and has been found in 10% to 60% of HCV-infected patients [ 16 - 18 ]. However, recent experimental studies have demonstrated that the HCV core protein interferes with insulin signaling by degrading insulin receptor substrate-1 by upregulating the expression of mammalian target of rapamycin (mTOR)/p70 ribosomal protein S6 kinase 1, suppressor of cytokine signaling 3, and tumor necrosis factor-α [ 19 , 20 ]; and downregulating glucose transporter 2,4 expression through upregulation of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase 2 [ 21 , 22 ].…”
Section: Clinical Impact Of Hcv Infection In Ckd Patientsmentioning
confidence: 99%
“…Além disso, a resistência à insulina está associada a um risco aumentado de desenvolver pré-diabetes e, possivelmente, diabetes mellitus tipo 2 (Alzahrani, 2022), doença cardiovascular e renal em pacientes com hepatite C crônica (Fabrizi;Donato;Messa, 2017). No presente estudo foi observada uma prevalência de 34% de resistência à insulina entre os portadores crônicos do HCV, e essa prevalência foi menor do que a descrita por Villar et al (2017). Esse estudo encontrou uma prevalência de 62% de resistência à insulina em 214 participantes com hepatite C crônica atendidos em um hospital no Rio de Janeiro (Villar et al, 2017), porém, nesse estudo foi utilizado um valor de corte menor para resistência à insulina (HOMA-IR > 2) quando comparado ao presente estudo (HOMA-IR ≥ 3).…”
Section: Discussionunclassified
“…No presente estudo foi observada uma prevalência de 34% de resistência à insulina entre os portadores crônicos do HCV, e essa prevalência foi menor do que a descrita por Villar et al (2017). Esse estudo encontrou uma prevalência de 62% de resistência à insulina em 214 participantes com hepatite C crônica atendidos em um hospital no Rio de Janeiro (Villar et al, 2017), porém, nesse estudo foi utilizado um valor de corte menor para resistência à insulina (HOMA-IR > 2) quando comparado ao presente estudo (HOMA-IR ≥ 3).…”
Section: Discussionunclassified